PENGENDALIAN RESISTENSI BAKTERI TERHADAP ANTIBIOTIK MELALUI PEMBERDAYAAN PEREMPUAN DALAM KELOMPOK MASYARAKAT - Sarmalina Simamora; Sarmadi .; Mona Rahmi Rulianti; Ferawati . Suzalin (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT, POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN PALEMBANG, 2021)
Antibiotics are needed to treat infections caused by pathogenic bacteria. The use of antibiotics to treat bacterial infections if done in an inappropriate manner can have detrimental consequences, both clinical and economic. Incorrect dosage, timing and frequency of use can cause resistance. From various studies in various places it was found that people's knowledge and behavior in using antibiotics is still not wise. The purpose of this activity is for participants to have good knowledge about the use of antibiotics. Partners were the mother of the arisan group were 29 people and the church women's group were 33 people. Measurement of knowledge was carried out by means of questionnaires and education was given orally and in writing by presenting a paper. The results showed an increase in knowledge about antibiotics in the good and very good categories, from 25.8% to 80.64% after education. The conclusion, their knowledge increase after education and can play a role in controlling bacterial resistance in their families and their community.